Shrub encroachment influences herbaceous communities in flooded grasslands of a neotropical savanna wetland. Issue 3 (7th February 2016) - Barbosa da Silva, Fernando Henrique; Arieira, Julia; Parolin, Pia; Nunes da Cunha, Cátia; Junk, Wolfgang Johannes
Abstract: Question: The encroachment of woody species has been globally reported over much of arid and semi‐arid biomes, and has been associated with a decrease in cover and number of herbaceous species. How does the encroachment of a woody shrub affect herbaceous community structure and species composition in grasslands of a wetland ecosystem? Location: Seasonally flooded grasslands in a Neotropical Hyperseasonal Savanna, the Pantanal wetland, Brazil. Methods: We investigated the effect of the encroaching plant Combretum laxum on a herbaceous community from seasonally flooded grasslands in the Pantanal wetland using 29 vegetation samples representing encroachment at different spatio‐temporal stages. The point quadrat method was used to acquire vegetation data, as plant cover, species richness (S) and Shannon‐Wiener diversity index (H'). We evaluated the existence of stages of encroachment related to differences in vegetation structure and species composition using non‐metric multidimensional scaling ordination and analysis of similarity. The response of the herbaceous community to shrub advance was analysed using linear and quadratic polynomial regression models. Model fitness was tested using the ACI. Results: The advance of the woody encroaching plant C. laxum over the seasonally flooded grassland occurs in three stages: grassland stage, shrub islands stage and shrubland stage . The initial advance of C. laxum over the grassland, represented by the shrub islands stage was correlated to an increase in species richness and a decrease in important native forage grasses. Critical changes in the herbaceous community were observed when the encroaching plant covered >30% of the periodically flooded grassland, when the richness of herbaceous species dropped from 22 to four. Conclusions: Woody encroachment causes impoverishment and simplification of the herbaceous community. The shift from a grass‐ to a shrub‐dominated state is related to the reduction in important grassland‐obligate species, forage resources for herbivore livestock and wild animals, affecting the ecological dynamics and the economy of rangelands. Conservation of these grassland ecosystems depends on rangeland management practices guided by scientific knowledge on the causes and consequences of plant community changes. Abstract : The encroachment of woody species has been globally reported over arid and semi‐arid biomes, and has been associated with a decrease in cover and number of herbaceous species. We examined the effects of shrubby encroachment over the herbaceous community in tropical floodable grasslands. We found that encroachment impoverishes the herbaceous community decreasing the cover of important forage resources.